MAXIMIZING COOLING ENERGY SAVINGS IN BUILDINGS WITH CLIMATE CHANGE: THE POTENTIAL OF PHASE CHANGE MATERIALS AND VENTILATION STRATEGIES - Khawaja, Saleh Ali (School of Engineering and Digital Sciences, 2023)
Due to climate change, the cooling energy demand in the building sector is projected to increase significantly. According to International Energy Agency, energy-efficient technologies should be implemented for a sustainable future. Phase change materials (PCM) potential for reducing building energy consumption have been widely acknowledged by researchers in the recent past. This research evaluates the implementation of PCM for building cooling energy savings (CES) with climate change and assesses the improvement in CES by coupling PCM with free night ventilation and changeover ventilation. Further, the performance of PCM is examined using novel indicators, energy charging, and discharging coefficients. For this purpose, hybrid downscaled weather data for 2095 were obtained, and 39 cities located in 13 different zones of the future Koppen-Geiger climate map were considered. A range of PCMs (PCM 18-32) were incorporated into the mid-rise apartment, and energy simulations were carried out using Energyplus. The results showed that the optimum PCM ranges from PCM27 to PCM30, and substantial CES (1555 kWh-7240 kWh) were obtained in all zones except Cfb, Dfa, and Dfb. The combination of PCM and free night ventilation significantly improved the CES by up to 35%. The CES was further improved up to 96% by coupling the changeover ventilation with PCM compared to the case with no ventilation and no PCM. Overall, coupling PCM with changeover ventilation appeared to be the best strategy for maximizing the CES in all climate zones.
Keywords: type of access: open access; Cooling energy saving; Climate change; Phase Change Material; Optimization; Performance Indicator; Natural ventilation